Nutritional characteristics of biofortified common beans - Brigide,Priscila (2014)
Iron and zinc deficiency can cause anemia and alterations in the immune response and impair work capacity. To minimize this problem, biofortification has been developed to improve and/or maintain the nutritional status of the population. Beans are an important source of carbohydrates, proteins, and minerals. The objective of this study is to characterize biofortified beans, quantify the minerals in different cultivars, and determine mineral dialysis. Grains of raw and cooked beans were analyzed for moisture, protein, lipids, fiber, minerals, and in vitro availability using four treatments and one control. The data were analyzed using ANOVA, and the Tukey test (p<0.05). The chemical composition of the raw and cooked treatments showed a moisture content ranging from 13.4 to 81.4%, protein from 22.24 to 31.59%, lipids from 1.66 to 2.22%, fiber from 16.81 to 40.63%, carbohydrates from 27.80 to 34.78%, and ash from 4.1 to 4.82%. Different varieties of beans showed statistically significant differences in iron and zinc content compared to the control cultivar (Pérola). The iron content differed significantly from that of the Pérola cultivar in the raw treatment, while in the cooked treatment, the control cultivar did not differ from the Piratã. The same behavior was observed for the zinc content in both treatments. There was no significant difference between the cultivars in the treatments in terms of the content of the dialysis of Calcium (Ca), Iron (Fe), Magnesium (Mg), and Zinc (Zn).